The Biblical Herem A Window in Israel's Religious Experience - Stern, Philip D. (Brown Judaic Studies, 2020)
The Biblical Herem: A Window on Israel's Religious Experience, was a groundbreaking, and controversial, examination of the herem, a biblical mode of declaring something (objects, people, cities) proscribed. Stern here reconstructs how the herem relates to other modes of thinking, in the Hebrew Bible and elsewhere in the Ancient Near East. The book contains a new preface by the author.